Effect of Passageway Width on Pedestrians Flow Characteristics in Intercity Railway Stations - Sala Eswar (Transport and Telecommunication, 2019)
Rail transportation is most economical means of the mode in comparison to road transportation. Intercity railway stations are nodal points of the rail network. With the growing demand and land use constraints, these are to be well planned, managed and designed. In intercity railways station infrastructure, passageways are confined and elevated elements for pedestrian movements to access among platforms to alight and board trains. Provision of appropriate width for passageway is of greater importance regarding comfort, convenient, evacuation, efficient, aesthetic, cost-effective, environment-friendly and well integrated with other elements of infrastructure. A proper understanding of pedestrian flow characteristics and affecting factors on passageway aids in design implications. In the present work, pedestrian flow characteristics variation on passageway and its width effect is studied. Results showed that, under normal conditions, flow rate (ped/m/min) and mean walking speed (m/min) reduces with increase in width (m). For a given flow rate, volume (ped/min) of pedestrians served on passageway increases with increase in width. Statistical tests revealed that there exists a significant difference in mean walking speed of pedestrians on passageways with different widths.